Transfusion efficacy and influencing factors of patients transfused with different therapeutic doses of platelets: a comparative analysis - ZHU Jianling; CHENG Tingting; MA Chunya; FU Lihui; SHI Hongmei; YU Yang (Zhongguo shuxue zazhi)
[Objective] To compare and analyze the efficacy of platelet transfusion in patients with different doses, and to analyze the risk factors for platelet transfusion refractoriness. [Methods] A total of 5 827 patients who received platelet transfusion in the PLA General Hospital from May 2023 to May 2024 were selected as the research subjects, among which 4 780 patients were transfused with 1 therapeutic dose of platelets, and 1 047 patients were transfused with 0.5 therapeutic dose of platelets, and the efficacy of platelet transfusion was compared between the two groups. The effects of gender, disease type, white blood cell count before transfusion, fever, number of platelet transfusions, and platelet antibodies on platelet transfusion refractoriness were analyzed using univariate analysis, and the independent risk factors affecting platelet transfusion refractoriness were further analyzed by multivariate logistic regression. [Results] Among 4 780 patients, 3553 (74.3%) were effective and 1 227 (25.7%) were ineffective. Among 1 047 patients, 0.5 platelet infusion was effective in 755 cases (72.1%) and ineffective in 292 cases (27.9%). There was no significant difference in the effective rate of platelet transfusion between the two groups (P>0.05). Univariate analysis showed that the therapeutic effect of platelet transfusion was related to age, the number of platelet transfusion, disease type, platelet antibodies and white blood cell count before transfusion (P<0.05), while age, gender, fever and blood type were not related to the therapeutic effect of platelet transfusion (P>0.05). The results of multi-factor analysis showed that age, white blood cell count >50×109/L, platelet transfusion times, disease type and platelet antibody were independent risk factors for ineffective transfusion (P<0.05). [Conclusion] There is no significant difference in the efficacy of platelet infusion with 0.5 therapeutic dose or 1 therapeutic dose. In addition, age, white blood cell count >50×109/L, the number of platelet transfusion, disease type and platelet antibodies were the factors affecting the ineffective platelet transfusion in group 2.